The Relationship between Leisure Satisfaction and Social Media Addictions of Individuals at University - Yesim Avunduk (Journal of Educational Issues, 2024)
This study aimed to determine the relationship between leisure satisfaction and social media addiction of university students. The study group of the research was formed by the voluntary participation of 193 students (133 male and 60 female), studying at the School of Physical Education and Sports of Istanbul Gelişim University. In addition to the personal information form, the “Leisure Satisfaction Scale (LSS)” developed by Beard and Raghep (1980) and adapted into Turkish by Gökçe and Orhan (2011), and the “Social Media Addiction Scale (SMAS)” developed by Bakır Ayğar and Uzun (2018) were used as data collection tools. After the data showed normal distribution in the Kolmogrov-Smirnov normality test, T-test, ANOVA and Pearson Correlation test were used in the analysis. The level of significance in the study was set at 0.05. In the research findings; gender and age groups of individuals affect their leisure time satisfaction levels; It has also been found that age groups affect social media addiction. As a result, it was determined that leisure satisfaction levels and social media addiction changed according to various variables of university students, and a negative significant relationship was found between leisure satisfaction and social media addiction.